2018
DOI: 10.1063/1.5011404
|View full text |Cite
|
Sign up to set email alerts
|

Thermal annealing and single–domain preparation in tetragonal Pb(In1/2Nb1/2)O3–Pb(Mg1/3Nb2/3)O3–PbTiO3 crystal for electro–optic and non–linear optical applications

Abstract: The relaxor–PbTiO3 single crystal has attracted extensive attention in ultrasound transducers, sensors, actuators, and optoelectronics devices due to its excellent piezoelectric response and electro–optic properties. Preparation of a single–domain crystal as a critical process for application in electro–optic and non–linear optical devices suffers from serious and inevitable cracking. Therefore, a pre-poling thermal annealing process was suggested to release residual stress from crystal growth and the ferroele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…An electric DC-field along <001> was applied to a tetragonal PIN-PMN-PT crystal at a temperature above T C , and then on cooling, only the <001>-oriented domain was formed while the formation of non-180 • domains was avoided. The reduced non-180 • ferroelectric domains decreased the strain variation, resulting in achieving a crack-free single domain [94,99]. The resulting single-domain crystal showed that there was no cost to the piezoelectricity but a high mechanical quality factor [94].…”
Section: Threshold DC Field and Over-poling Effectmentioning
confidence: 99%
“…An electric DC-field along <001> was applied to a tetragonal PIN-PMN-PT crystal at a temperature above T C , and then on cooling, only the <001>-oriented domain was formed while the formation of non-180 • domains was avoided. The reduced non-180 • ferroelectric domains decreased the strain variation, resulting in achieving a crack-free single domain [94,99]. The resulting single-domain crystal showed that there was no cost to the piezoelectricity but a high mechanical quality factor [94].…”
Section: Threshold DC Field and Over-poling Effectmentioning
confidence: 99%
“…The recently developed methods for achieving a single domain state [6], as well as suitable uniformity and possibility of preparing crystals of the optical quality made PMN-PT a promising object for domain engineering by creation of precise periodical domain structures [7]. Domain engineering requires nondestructive methods with high spatial resolution for inspection of the domain wall positions both at the surface and in the crystal bulk [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The as-grown sample was annealed at 750 C for 10 h to release the stresses produced by crystal growth and mechanical treatment. 20 The crystal composition was confirmed by dielectric measurements using the dependence of temperature of maximum permittivity T m on the composition of (1-x)PMN-xPT according to the following formula (see the supplementary material for dielectric measurements) 21,22 x ¼ T m þ 12 C 527 C :…”
mentioning
confidence: 99%